Analysis of Learning Difficulties of History Education Students in Quantitative Research Methodology Courses - Moh. Imron Rosidi; Ismaul Fitroh (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2026)
The Quantitative Research Methodology course is a compulsory course in the History Education Study Program that requires analytical and logical thinking skills, as well as skills in processing and interpreting statistical data. However, in practice, there are still students who have difficulty understanding statistical concepts, developing research instruments, and analyzing quantitative data. This condition is reflected in the distribution of student grades in the odd semester of the 2025/2026 Academic Year, which shows that most students are in the middle grade category and there are still low achievements. This problem indicates that there are learning obstacles that need to be studied systematically. This study aims to describe the level and factors causing student learning difficulties in the Quantitative Research Methodology course. The method used is qualitative descriptive with 22 students as research subjects. The research instrument is a Likert scale questionnaire consisting of 15 statements covering aspects of interest, motivation, basic abilities, mastery of material, learning models, the role of lecturers, classroom conditions, and learning resources. The data are analyzed through percentage calculations and classified into low, medium, and high categories. The results of the study indicate that the level of learning difficulties experienced by students is in the moderate category, with an average of 72%. The dominant factors stem from the learning model and the role of lecturers, accompanied by students' basic abilities and learning resources.